CLINICAL EVALUATION OF PRIMARY ENDOCARDIAL FIBROELASTOSIS: A STUDY OF LIVING AND POST MORTEM CASES - HIRONO, KAZUKI; ONO, SANAYASU; KOBAYASHI, TOSHIHIRO; TASHIRO, MASAHIKO; KOSUDA, TAKASHI; TABATA, HIROSHI; KOBAYASHI, TOMIO; SONE, KATSUHIKO (The KITAKANTO Medical Journal, 1992)
Primary endocardial fibroelastosis (EFE) is a cardiomyopathy of unknown origin that affects infants and young children. We treated 6 cases of EFE. 4 cases are alive and 2 cases died. The important prognostic factors are : duration of untreated period, low voltage and extremely high voltage in the left chest leads of the electrocardiogram and a high degree of fibroelastosis histologically. The LV functions of the 3 living cases have not improved on echocardiography despite intensive treatment, so careful follow up is necessary.